The Impact of Development Policies on Community Empowerment in Rural Areas - Syafaruddin Syafaruddin (Green Inflation: International Journal of Management and Strategic Business Leadership, 2025)
This research examines the influence of development policies on community empowerment in rural areas. Using a mixed-methods approach combining quantitative surveys (n=400) across four diverse rural districts with qualitative interviews (n=40) and focus group discussions (n=12), the study identifies key factors affecting the success of empowerment programs. Findings reveal that community participation in planning phases and equitable access to resources (financial, informational, and material) are fundamental determinants of successful rural empowerment. The research demonstrates that development policies are most effective when they: (1) enable genuine participation beyond mere consultation, (2) build on existing community institutions, (3) address power imbalances within communities, and (4) provide appropriate external facilitation. Statistical analysis shows strong correlations between empowerment outcomes and participation in planning (β=0.73, p<0.001) and access to financial resources (β=0.68, p<0.001). This study contributes to the theoretical understanding of empowerment processes and practical knowledge for policymakers and practitioners seeking to design more effective community development interventions in rural contexts.